Design and experimental study of an origami-inspired constant-force mechanism. (January 2023) - Liu, Shiwei; Peng, Gaoliang; Li, Zhixiong; Li, Weihua; Jin, Kang; Lin, Hongzhao
Abstract: Inspired by the strong nonlinearity of origami cartons, a novel origami-inspired constant-force mechanism (OriCFM) is systematically studied for obtaining a stable quasi-static constant force output. The proposed OriCFM is evolved by adding equivalent springs at horizontal and oblique creases of the rigid origami mechanism. Based on the geometry relationship, the mechanical model of the origami carton is established and its zero-stiffness is obtained. The influence of structural parameters and spring stiffness on the constant force characteristic of the OriCFM is analyzed in detail. By configuring different numbers of horizontal springs, various output characteristics could be observed in the prototype experiment. The case of 4 oblique springs and 2 horizontal springs exhibited partial constant-force output, and the constant-force range accounted for 48.54% of the total experimental stroke. Comparisons of theoretical results with experimental data were carried out to demonstrate the feasibility and effectiveness of the proposed origami-inspired mechanism. The outcomes of this work could expand the applications of origami mechanisms and promote the development of low-stiffness systems. Highlights: A novel origami-inspired constant-force mechanism (OriCFM) is proposed. The OriCFM can achieve stable force output in a large constant-force range. With influential and tunable parameters, the OriCFM has strong design flexibility. The quasi-static output of OriCFM is verified by numerical and experimental studies.